Corruption trials in Argentina: justice delayed? - Elias, Friederike; Pereyra, Sebastián (Political corruption and organizational crime, 2021)
This chapter is devoted to the role of the judicial system in Argentina’s corruption problem. Argentina has been dealing with the problem of political corruption on a recurring basis for three decades. Complaints, scandals and judicial investigations have cyclically targeted governments and officials from the 1990s onwards. Over the years, a large number of judicial cases have been opened in corruption cases with high public visibility, but they have not yielded results, thus generating a significant gap between the volume of complaints and the results of judicial decisions.